2015
DOI: 10.1049/iet-its.2014.0090
|View full text |Cite
|
Sign up to set email alerts
|

Vacant parking area estimation through background subtraction and transience map analysis

Abstract: Abstract:A method for estimating the dimensions of non-delimited free parking areas by using a static surveillance camera is proposed. The proposed method is specially designed to tackle the main challenges of urban scenarios (multiple moving objects, outdoor illumination conditions and occlusions between vehicles) with no training. The core of this work is the temporal analysis of the video frames to detect the occupancy variation of the parking areas. Two techniques are combined: background subtraction using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…However, the presented work shows less precision and also not fully integrated into a distributed ITS system. Other related works that use smart camera for parking lots monitoring can be found in [13][14][15][16].…”
Section: Related Workmentioning
confidence: 99%
“…However, the presented work shows less precision and also not fully integrated into a distributed ITS system. Other related works that use smart camera for parking lots monitoring can be found in [13][14][15][16].…”
Section: Related Workmentioning
confidence: 99%
“…In detecting vehicles and parking spaces, Ling et al [4] used IoT technology to detect parking spaces for vehicles and developed a notification system. Postigo et al [8] used background subtraction method for vehicle detection and counting. Yu et al [11] established a prediction model for parking space usage based on the historical data of reconnaissance vacancies.…”
Section: Related Workmentioning
confidence: 99%
“…Occupancy is detected when the green dots become invisible due to a parked car. Postigo, et al [12] suggested a computationally efficient method for parking area estimation. Their method is to perform background subtraction and create a transience map, which in turn will be used for occupancy detection.…”
Section: Related Workmentioning
confidence: 99%